Does option complexity contribute to the framing effect, loss aversion, and delay discounting in younger and older adults? - Veronika Zilker; Thorsten Pachur (Journal of Behavioral Decision Making, 2021)
Recent findings suggest that the commonly observed preference for a safe over a risky option, which is more pronounced in older than in younger adults, is largely driven by differences in the complexity of those options. Here we examine whether option complexity also contributes to the emergence of the framing effect and loss aversion in risky choice as well as to delay discounting in intertemporal choice. All of these phenomena tend to be measured with choice problems that involve options differing in complexity. We also examine whether option complexity contributes to potential age differences in these phenomena. In each paradigm, we experimentally increased the complexity of the simpler option, thus reducing differences in the complexity of the options. We found no evidence for an effect of this manipulation on the framing effect nor on participants' preferences in the loss aversion task. On average, participants did not show loss aversion. Increasing the complexity of the option with an immediate reward in the intertemporal choice task made younger, but unexpectedly not older, adults less likely to choose this option. Our results thus indicate that preferences in tasks typically used to measure the framing effect, loss aversion, and delay discounting are only little affected by differences in option complexity.
Keywords: 650; aging; delay discounting; framing effect; loss aversion; option complexity; risky choice